Embryonic germ cells from mice and rats exhibit properties consistent with a generic pluripotent ground state - Leitch, Harry G. (Company of Biologists, 2010)
Mouse and rat embryonic stem cells can be sustained in defined medium by dual inhibition (2i) of the mitogen-activated protein kinase (Erk1/2) cascade and of glycogen synthase kinase 3. The inhibitors suppress differentiation and enable self-renewal of pluripotent cells that are ex vivo counterparts of naïve epiblast cells in the mature blastocyst. Pluripotent stem cell lines can also be derived from unipotent primordial germ cells via a poorly understood process of epigenetic reprogramming. These are termed embryonic germ (EG) cells to denote their distinct origin. Here we investigate whether EG cell self-renewal and derivation are supported by 2i. We report that mouse EG cells can be established with high efficiency using 2i in combination with the cytokine leukaemia inhibitory factor (LIF). Furthermore, addition of fibroblast growth factor or stem cell factor is unnecessary using 2i-LIF. The derived EG cells contribute extensively to healthy chimaeric mice, including to the germline. Using the same conditions, we describe the first derivations of EG cells from the rat. Rat EG cells express a similar marker profile to rat and mouse ES cells. They have a diploid karyotype, can be clonally expanded and genetically manipulated, and are competent for multilineage colonisation of chimaeras. These findings lend support to the postulate of a conserved molecular ground state in pluripotent rodent cells. Future research will determine the extent to which this is maintained in other mammals and whether, in some species, primordial germ cells might be a more tractable source than epiblast for the capture of naïve pluripotent stem cells.